The psychiatric interview - Carlat, Daniel J. (Practical guides in psychiatry., 2017)
This handbook is a guide to every aspect of the psychiatric interview. It begins with general principles of effective interviewing, including techniques for approaching threatening topics, improving patient recall, and dealing with challenging patients.